Frequency independent-dependent conductivity and dielectric properties of some ionomers - Yakuphanoğlu, Fahrettin; Erten, H (Wiley, 2005)
The preparation and physical properties of some ionomers have been investigated. The addition of CH3I significantly improved the conductivity of the ionomers. At room temperature, the highest ionic conductivity value was found to be 4.93 10(-8) S cm(-1) in the 14 ionomer. The conductivity data do not obey the Arrhenius law and the non-linearity indicates ionic transport. The alternating current conductivity parameters and dielectric constants of the ionomers were determined. (c) 2005 Society of Chemical Industry.
Keywords: ionic conductivity; dielectric permittivity; ionomer